Validation of the Functional Assessment of Cancer Therapy–Leukemia instrument in patients with acute myeloid leukemia who are not candidates for intensive therapy. Issue 15 (28th May 2020) - Peipert, John Devin; Yount, Susan E.; Efficace, Fabio; Loefgren, Christina; Pierson, Renee; He, Jianming; Cella, David
Abstract : Background: The objective of this study was to validate the Functional Assessment of Cancer Therapy–Leukemia (FACT‐Leu) in patients with acute myeloid leukemia (AML) who are not candidates for intensive therapy. Methods: A sample of 317 patients with AML who were not eligible for intensive chemotherapy completed the FACT‐Leu and EuroQol 5‐Dimension (EQ‐5D) measures (Utility Index and Visual Analogue Scale) every 28 days until the end of treatment. Internal consistency reliability was estimated with Cronbach's α. Concurrent validity was examined with correlations between FACT‐Leu and EQ‐5D scales, and known‐groups validity was examined by determining whether FACT‐Leu scales distinguished between Eastern Cooperative Oncology Group (ECOG) performance status ratings (PSRs) and between maximum adverse event toxicities at the baseline. This study examined responsiveness to change by anchoring change in the FACT‐Leu scales to a 0.10 change in the EQ‐5D Health Utility Index. Results: Cronbach's α usually exceeded the threshold for good (≥0.80) or excellent reliability (≥0.90). Correlations between FACT‐Leu and EQ‐5D scales were moderate ( r  > 0.50) or high ( r  > 0.70). FACT‐Leu scales distinguished between ECOG PSR groups with large effect sizes for an ECOG PSR of 0 versus an ECOG PSR of 2 (0.50 ≤  d  < 0.80). In addition, Functional Assessment of Cancer Therapy–General, Additional Concerns, FACT‐Leu Total, and Trial Outcomes Index scales distinguished between patients with grade 3 or lower maximum adverse event toxicities and those with maximum adverse event toxicities higher than grade 3, but effect sizes were small ( d  < 0.50). Finally, FACT‐Leu scale coefficients for a 0.10 change in the 5‐level version of the EQ‐5D HUI ranged between −0.01 and 4.30. Conclusions: The FACT‐Leu is a suitable outcome measure for AML clinical trials among patients not eligible for intensive therapy, and it may have value for clinical monitoring. Abstract : Regulators seek appropriate patient‐reported outcomes for acute myeloid leukemia clinical trials. This study demonstrates the reliability, validity, and responsiveness of the Functional Assessment of Cancer Therapy–Leukemia among patients with acute myeloid leukemia who are not candidates for intensive therapy.